Social Media Engagement and Small and Medium Enterprise (SME) Performance in Awka South’s Informal Sector, Nigeria - Taiwo Abdulahi (Saniya Institute, 2025)
Small and Medium Enterprises (SMEs) play a critical role in economic growth and employment creation in Nigeria, yet many struggle with visibility, customer engagement, and sustainable profitability. This study examined how consumer engagement on social media can be leveraged to improve the performance of informal SMEs in the Awka South Local Government Area of Anambra State. Data were collected through a structured questionnaire administered to 100 registered SMEs, and analysed using descriptive statistics, Pearson Product-Moment Correlation (PPMC) and Linear Regression. The findings revealed that consumer engagement on social media significantly contributes to SME performance by improving sales, customer retention, and brand visibility. The type of social media platform used by informal SMEs in promoting their business was found to be a vital tool for retaining customers. In contrast, the rate at which consumers engage with SMEs' posts was associated with SMEs' brand recognition. Furthermore, consumer interaction on social media was strongly positively correlated with SME sales growth (r = 0.784, p < 0.05). The study concludes that consumer engagement on social media is a vital tool for scaling up the performance of informal SMEs when used strategically and consistently. It recommends that informal SMEs pay attention to consumer engagement on social media strategies, invest in capacity building on digital tools, and that policymakers provide supportive digital infrastructure to enhance informal SMEs' growth.